DNA methylation in cocaine use disorder - an epigenome-wide approach in the human prefrontal cortex - Zillich, Eric; Zillich, Lea; Streit, Fabian; Frank, Josef; Friske, Marion; Foo, Jerome Clifford; Mechawar, Naguib; Turecki, Gustavo; Hansson, Anita C.; Nöthen, Markus M.; Rietschel, Marcella; Spanagel, Rainer; et al. (Frontiers in psychiatry, 2023)
BackgroundCocaine use disorder (CUD) is characterized by a loss of control over cocaine intake and is associated with structural, functional, and molecular alterations in the human brain. At the molecular level, epigenetic alterations are hypothesized to contribute to the higher-level functional and structural brain changes observed in CUD. Most evidence of cocaine-associated epigenetic changes comes from animal studies while only a few studies have been performed using human tissue.MethodsWe investigated epigenome-wide DNA methylation (DNAm) signatures of CUD in human post-mortem brain tissue of Brodmann area 9 (BA9). A total of N = 42 BA9 brain samples were obtained from N = 21 individuals with CUD and N = 21 individuals without a CUD diagnosis. We performed an epigenome-wide association study (EWAS) and analyzed CUD-associated differentially methylated regions (DMRs). To assess the functional role of CUD-associated differential methylation, we performed Gene Ontology (GO) enrichment analyses and characterized co-methylation networks using a weighted correlation network analysis. We further investigated epigenetic age in CUD using epigenetic clocks for the assessment of biological age.ResultsWhile no cytosine-phosphate-guanine (CpG) site was associated with CUD at epigenome-wide significance in BA9, we detected a total of 20 CUD-associated DMRs. After annotation of DMRs to genes, we identified Neuropeptide FF Receptor 2 (NPFFR2) and Kalirin RhoGEF Kinase (KALRN) for which a previous role in the behavioral response to cocaine in rodents is known. Three of the four identified CUD-associated co-methylation modules were functionally related to neurotransmission and neuroplasticity. Protein-protein interaction (PPI) networks derived from module hub genes revealed several addiction-related genes as highly connected nodes such as Calcium Voltage-Gated Channel Subunit Alpha1 C (CACNA1C), Nuclear Receptor Subfamily 3 Group C Member 1 (NR3C1), and Jun Proto-Oncogene, AP-1 Transcription Factor Subunit (JUN). In BA9, we observed a trend toward epigenetic age acceleration (EAA) in individuals with CUD remaining stable even after adjustment for covariates.ConclusionResults from our study highlight that CUD is associated with epigenome-wide differences in DNAm levels in BA9 particularly related to synaptic signaling and neuroplasticity. This supports findings from previous studies that report on the strong impact of cocaine on neurocircuits in the human prefrontal cortex (PFC). Further studies are needed to follow up on the role of epigenetic alterations in CUD focusing on the integration of epigenetic signatures with transcriptomic and proteomic data.